ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN PERKAPITA DI PROVINSI JAWA TENGAH - Arifin, Muhammad Zainal (Jurnal Bina Bangsa Ekonomika, 2025)
Per capita income is used to describe the economic conditions in an area played by the community. The amount of per capita income in each region is not the same, so there is an Income Gap between Regions and it becomes a problem of economic equality, especially in countries where welfare is still relatively low. People with high income levels can have their basic needs met so that they tend to develop more easily because they have a prosperous life, while people with low-income levels have limitations in realizing a more prosperous life. This study was conducted to determine the causes of income imbalances between regions using data covering 29 districts and 6 cities. The independent variables of this study include Population, Human Development Index, Average Wages and Number of Tourist Villages. The method used to compile the study was carried out using a panel data regression model. The results of the calculation of the selected model are the Fixed Effect Model (FEM). Therefore, the purpose of this study is to determine whether the independent variables affect per capita income in Central Java in 2019–2023